Root foraging in response to heterogeneous soil moisture in two grapevines that differ in potential growth rate - Bauerle, Taryn L (The New phytologist, 2008)
* Linkages between plant growth rate and root responses to soil moisture heterogeneity were investigated. * Root dynamics were studied using genetically identical shoots (Vitis vinifera cv. Merlot) with genetically distinct root systems that promote higher (HSV) and lower (LSV) shoot growth rates (1103P and 101-14 Mgt, respectively). Three quantities of irrigation replenished different amounts of evapotranspiration (0, 40 and 100%ET(c)) in a California vineyard. * Roots of HSV vines exhibited more plasticity, as indicated by greater preferential growth in irrigated soil during the summer, and a larger shift in root diameter with a change in soil moisture than LSV vines. Higher tolerance of low soil moisture was not observed in LSV roots--root survivorship was similar for the two rootstocks. LSV vines produced a large fraction of its roots during the winter months and increased root density over the study, while HSV vines produced roots mainly in summer and only exhibited a high initial peak in root biomass in the first year. * These results demonstrated that a plant of higher vigor has greater morphological plasticity in response to lateral heterogeneity in soil moisture but similar tolerance to moisture stress as indicated by root survivorship in dry soil